2012
DOI: 10.1093/eurpub/cks124
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work factors and sickness absence in 31 countries in Europe

Abstract: Various psychosocial work factors were found to be associated with sickness absence. A less conservative analysis exploring each factor separately provided a still higher number of risk factors. Preventive measures should take psychosocial work environment more comprehensively into account to reduce sickness absence and improve health at work at European level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
121
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(138 citation statements)
references
References 36 publications
13
121
2
2
Order By: Relevance
“…have found high job demands (19) and low control (55) as predictors of sickness absence. One of the reasons why we chose to look at the combined job strain measure instead of demands and control separately was that it has been shown that job strain (even without positive interaction between job demands and control) predicts outcomes such as coronary heart disease better than low job control, when analyses are adjusted for socioeconomic status (56).…”
Section: Mortensen Et Almentioning
confidence: 99%
See 3 more Smart Citations
“…have found high job demands (19) and low control (55) as predictors of sickness absence. One of the reasons why we chose to look at the combined job strain measure instead of demands and control separately was that it has been shown that job strain (even without positive interaction between job demands and control) predicts outcomes such as coronary heart disease better than low job control, when analyses are adjusted for socioeconomic status (56).…”
Section: Mortensen Et Almentioning
confidence: 99%
“…A systematic review found that long work hours predict sickness absence and ill health (68), while another study found no association (69). A meta-analysis actually found that long working hours was a protective factor against sickness absence (19). The authors suggested the healthy worker effect as a plausible explanation and that some individuals with long working hours have highly demanding jobs and may feel pressure to be working even though they are sick (19).…”
Section: Mortensen Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…To develop, improve and implement effective sick-leave prevention measures, we need to understand the risk factors. Previous research on the work environment and sickness absence has mainly focused on physical working conditions (1,2) and psychosocial factors such as job demands and control (3)(4)(5). Less is known about how and when workplace bullying is related to sickness absence, beyond cross-sectional studies demonstrating associations between the two.…”
mentioning
confidence: 99%